Antifouling Polymer Brushes Displaying Antithrombogenic Surface Properties - de los Santos Pereira, Andres; Sheikh, Sonia; Blaszykowski, Christophe; Pop-Georgievski, Ognen; Fedorov, Kiril; Thompson, Michael; Rodriguez-Emmenegger, Cesar (Biomacromolecules, 2016)
The contact of blood with artificial materials generally leads to immediate protein adsorption (fouling), which mediates subsequent biological processes such as platelet adhesion and activation leading to thrombosis. Recent progress in the preparation of surfaces able to prevent protein fouling offers a potential avenue to mitigate this undesirable effect. In the present contribution, we have prepared several types of state-of-the-art antifouling polymer brushes on polycarbonate plastic substrate, and investigated their ability to prevent platelet adhesion and thrombus formation under dynamic flow conditions using human blood. Moreover, we compared the ability of such brushes--grafted on quartz via an adlayer analogous to that used on polycarbonate--to prevent protein adsorption from human blood plasma, assessed for the first time by means of an ultrahigh frequency acoustic wave sensor. Results show that the prevention of such a phenomenon constitutes one promising route toward enhanced resistance to thrombus formation, and suggest that antifouling polymer brushes could be of service in biomedical applications requiring extensive blood-material surface contact.
Keywords: křemen; Polycarboxylate Cement; polykarboxylátový cement; Humans; povrchové vlastnosti; Quartz; lidé; adhezivita trombocytů; Platelet Adhesiveness; Surface Properties